Analisis Prosedur Pelaksanaan Itsbat Nikah Terhadap Perkawinan Sirri Berdasarkan Putusan Nomor : 473/PDT.P/2022/PA.LLG di Pengadilan Agama Lubuklinggau Kelas 1 B - Agustinus Samosir; Rheza Dwi Kristiani; Fitriyani Fitriyani (Fakultas Hukum, Universitas Warmadewa, 2024)
The procedure for implementing itsbat nikah provides legal protection because they obtain legal certainty from their marriage bond, so that all their rights can be recognized and protected. The purpose of this study is to find out and analyze the procedures for carrying out itsbat nikah, judges' considerations in deciding itsbat nikah cases and the factors that cause the applicant to apply for itsbat nikah based on decision number: 473/pdt.p/2022/PA.LLG. This type of research in legal research includes normative-empirical research. The approach used in this study is a legal approach in the form of legal norms, namely Law of the Republic of Indonesia Number 16 of 2019 amendments to Law Number 1 of 1974 concerning Marriage, and the Compilation of Islamic Law. The data collection techniques used are primary data and secondary data. The results of the study show that the procedure for implementing itsbat nikah is in accordance with the Book II Guidelines for the Implementation of Duties and Work Procedures of the Religious Courts. Consideration of the panel of judges in granting the itsbat of marriage to a siri marriage if it is in accordance with the pillars and conditions of Islamic marriage as well as the legal basis considerations, examines the case, its benefits, and puts forward syar'i arguments in its deliberations. The factor that became the reason for the applicant submitting hisbat marriage based on the decision number: 473/pdt.p/2022/PA.LLG was to complete the Umrah registration requirement investigators focus on Law Number 16 of 2019 concerning amendments to Law Number 1 of 1974 concerning marriage.